Independent work of students at linguistic universities: expectation and reality (Eurasian Journal of Philology Science and Education, 2021)
The article dwells upon independent work of students studying English. The author clarifies that independent work is understood as a form of organizing students’ learning, carried out directly or indirectly by a teacher. According to the author, theoretical and methodological basis relies on the fundamental and applied works of leading Kazakh and foreign authors. The author of the article describes what independent work is focused on and what its role is. It is specified that higher school has slightly different requirements for the student to organize independent work. The article presents the results of a survey among language school students from the first to the fourth years of studying to determine their priority academic skills. The author identifies the interrelationship between independent work in higher and secondary schools within the framework of the updated curriculum. It is noted what kind of independent work is carried out by students in the early stages of education and in the senior years of studying at the university. The author also tells about independent work when developing all types of foreign speech activity. The author emphasizes that independent work of students in the conditions of distance learning requires additional assistance and advice from the teacher. In addition, the author lists applications and websites that can be used by the teacher to organize and conduct independent work in the context of distance learning. Key words: independent work, distance learning, skills and abilities, self-learning